An Expectation-Based Approach to Explaining the Crossmodal Influence of Color on Orthonasal Odor Identification: The Influence of Expertise - Shankar, M; Simons, C; Shiv, B; McClure, S; Spence, C (2010)
In a previous series of experiments, the present authors demonstrated that when people are asked to identify the flavors of various drinks on the basis of orthonasal olfactory cues, their judgments are sometimes influenced by the colors of the drinks. Here, we explored the role that expertise plays in mediating color-flavor interactions. Non-experts and flavor experts took part in an odor identification task in which they smelled a number of drinks whose flavors were incongruent with what their colors would suggest. When a particular color, identified by participants as being one that generated a strong flavor expectation, was added to these drinks (as compared to when no such color was added), a significantly greater proportion of both non-expert and flavor expert participants' identification responses were consistent with this expectation. No significant difference in response behavior was found between these two groups of participants. Using a novel experimental approach that controlled for individual differences, the results of the present study add to the literature showing that flavor experts are not only susceptible to color-induced olfactory biases but perform no differently than non-experts in olfactory identification tasks. © 2010 Springer Science + Business Media, LLC.